Caracterização microestrutural e modelagem do amaciamento dinâmico a quente do aço inoxidável austenítico ASTM F 138, utilizado em implantes ortopédicos - Geronimo, Fabio Henrique Casarini (2014)
Flow stress curves of ASTM F 138 austenitic stainless steel were obtained through isothermal hot torsion testing in the temperature range of 900- 1200oC and in the strain rate range of 0,01-10s-1, totaling 24 experiments. To understand the dynamic softening during hot working of this material, the shape of the flow stress curves and the parameters required to calculate activation energy for hot working were evaluated. Also, the semi-empirical equations describing these parameters as function of Zener-Hollomon parameter (Z) were obtained. Mathematical modeling of flow stress curves was developed taking into account the recovery parameter r and the Avrami exponent n. Processing maps were constructed using the Dynamic Materials Model. The attained microstructures were analyzed by optical microscopy and the microstructure evolutions under some processing conditions were evaluated by EBSD technique. These procedures were also used to obtain the recrystallized fraction, to identify what softening mechanism was operating and in which conditions it becomes more active. Due to the intermediate stacking fault energy level in this material (78mJ/m2), attained data indicate that dynamic softening occurs in a balance between dynamic recovery and dynamic recrystallization, with temperature having a determining role. At higher Z, extended dynamic recovery takes place and dynamic recrystallization becomes incomplete due to plastic instabilities such as localized flow. Lower Z values offer favorable conditions for complete dynamic recrystallization, even if were necessary to impose large straining.